Recyclable Enantioselective Catalysts Based on Copper(II) Complexes of 2‐(Pyridine‐2‐yl)imidazolidine‐4‐thione: Their Application in Asymmetric Henry Reactions. Issue 15 (16th June 2016) - Nováková, Gabriela; Drabina, Pavel; Frumarová, Božena; Sedlák, Miloš
Abstract: This paper describes the preparation of enantioselective catalysts based on derivatives of imidazolidine‐4‐thione and their subsequent anchoring by means of a sulfur atom on a polymeric carrier. First, we verified the catalytic activity and enantioselectivity in the Henry reaction of the homogeneous variants of the catalysts, i.e., the copper(II) complexes of 2‐(pyridine‐2‐yl)imidazolidine‐4‐thiones and 4‐benzylsufanyl‐2‐(pyridine‐2‐yl)imidazolines themselves. It was found that these catalysts exhibit high enantioselectivity (up to 98% ee ). Subsequently, the imidazolidine‐4‐thione catalysts were immobilized by anchoring to polymeric carriers based on a copolymer of styrene and 4‐vinylbenzyl chloride. These heterogeneous catalysts were analogously tested with regard to their catalytic activity and enantioselectivity in the Henry reaction, and moreover, the possibility of their separation and reuse was studied. It was found that all the prepared immobilized catalysts are highly enantioselective (up to 97% ee ). Their recycling ability was tested in Henry reaction of 2‐methoxybenzaldehyde with nitromethane. It was found that they can be recycled more than ten times without any decrease of their enantioselectivity. Therefore, they present a better means of catalysis than the original copper(II) complexes of imidazolidine‐4‐ones from both economic as well as ecological points of view. Thus, such immobilized catalysts exhibit high application potential for the asymmetric Henry reaction. Abstract :